Encouraging Vietnamese-American Women to Obtain Pap Tests Through Lay Health Worker Outreach and Media Education - Lam, Tram K (Blackwell Science Inc, 2003)
BACKGROUND: Five times more Vietnamese-American women develop cervical cancer than white women. Few studies have examined whether community-based participatory research can effectively address Asian immigrants' health problems. This article reports the preliminary evaluation of 1 such project. METHODS: A coalition of 11 organizations in Santa Clara County, California worked with university researchers to design and simultaneously implement a media education (ME) campaign and a lay health worker outreach (LHWO) program to increase Vietnamese-American women's cervical cancer awareness, knowledge, and screening. Two agencies each recruited 10 lay health workers (LHWs), who, in turn, each recruited 20 women who were then randomized into 2 groups: 10 to LHWO+ME (n = 200) and 10 to ME alone (n = 200). LHWs organized meetings with women to increase their knowledge and to motivate them to obtain Pap tests. Participants completed pre- and post-intervention questionnaires. RESULTS: At post-intervention, significantly more LHWO+ME women understood that human papillomavirus and smoking cause cervical cancer. The number of women who had obtained a Pap test increased significantly among women in both LHWO+ME and ME groups, but substantially more in the LHWO+ME group. Significantly more LHWO+ME women said they intended to have a Pap test. CONCLUSIONS: Media education campaigns can increase Vietnamese women's awareness of the importance of Pap tests, but lay health workers are more effective at encouraging women to actually obtain the tests. Lay health workers are effective because they use their cultural knowledge and social networks to create change. Researchers, community members, and community-based organizations can share expert knowledge and skills, and build one another's capacities.